Republic of drivers : a cultural history of automobility in America - Seiler, Cotten (University of Chicago Press, 2008)
Rising gas prices, sprawl and congestion, global warming, even obesity--driving is a factor in many of the most contentious issues of our time. So how did we get here? How did automobile use become so vital to the identity of Americans? Republic of Drivers looks back at the period between 1895 and 1961--from the founding of the first automobile factory in America to the creation of the Interstate Highway System--to find out how driving evolved into a crucial symbol of freedom and agency. Cotten Seiler combs through a vast number of historical, social scientific, philosophical, and literary source.